Pengaruh Komitmen Organisasi, Prestasi Kerja, dan Sistem Imbalan terhadap Kepuasan Kerja Karyawan (Studi Perusahaan Perbankan di Sulawesi Selatan) - Muhammad Idrus Taba (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aims to investigate (1) the effects of incentive systems to organizational commitment; (2) the effects of incentive systems to staff’s performance; (3) the effects of incentive systems to staff’s satisfaction; (4) the effects of organizational staff’s commitment to staff’s performance; (5) the effects of organizational commitment to staff’s satisfaction; and (6) the effects of staff’s performance to satisfaction. This research involved 244 respondents who are working at the executive level in banking industries which are classified as national owned companies and local government owned bank in South Sulawesi. The methodnof analysis employs an integrated factors analysis with simultaneous regression of the structural equation modeling. The study results indicated that: (1) the incentive systems have directly effect’s, significant, and positive to organizational commitment; (2) Incentive systems did not affect significantly to performance, however, the effects could be indirectly and positively affected throught the organizational commitment. (3) Incentive systems are positively, directly and significantly affecting the staff’s satisfaction; (4) Organizational commitment have positively, directly and significantly affected the staff’s performance; (5) Organizational commitments have not significantly affected the staff’s satisfaction; (6) Performance have positively, directly and significantly affected the staff’s satisfaction. The normative (organizational) commitments of the staff’s t be more dominant compare to two others types of organizational commitment, i.e; affection and sustainable commitment. In fact, this normative type of organizational commitment affects to staffs performance, but, on the other hand, it has no affect on the staff’s satisfaction it all. In additon, the incentive systems, however well believed to be appropriate, nevertheless it has no direct affect on the staff’s performance (in which could only grow throught the organziational commitment) but it affect, positively to the staffs satisfaction.Keywords: Commitment, Job Satisfaction, Job Performance